ASSESSMENT OF AIR POLLUTION LEVEL OF NITROGEN DIOXIDE AND TRENDS OF IT CHANGES IN THE CITIES OF UKRAINE - Yatsenko, Y.; Shevchenko О.; Snizhko, S. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The purpose of the work is to study the current level and the main trends of atmospheric air pollution of the cities of Ukraine with nitrogen dioxide to identify the most polluted cities, their ranking to determine the list of cities for the priority implementation of environmental measures. For the purpose of the study, the information of the Central Geophysical Observatory on the average annual concentrations of nitrogen dioxide in the air of 51 cities of Ukraine for the period 1998-2015 was used. The study used the classical methods of applied mathematical statistics (estimation of statistical parameters of distribution of concentrations, construction of time trends on the method of least squares, graphical methods of visualization of levels of air pollution), which were implemented using the available programs "MS-Excell" and "Statistica-8.0". The classification of cities according to the level of MPC exceeds average annual concentrations of nitrogen dioxide. 3 groups of cities were allocated: 1 group (21 cities) permissible level of pollution (<1 MPC); 2 group (27 cities) – increased level of pollution (1-2 MPC); group 3 (3 cities) – high level of pollution (2-3 MPC). It has been established that in the air of 21 cities (41% of all cities where nitrogen dioxide is monitored in the atmosphere) of 51 cities, there is an acceptable level of air pollution. In the remaining cities (59%) – there is a stable excess of MPC. In 23 cities, even the minimum concentrations of NO2 exceed the permissible standards. The study of long-term dynamics of nitrogen dioxide in air has shown that the increase of concentrations of this pollutant for 1998-2015 is observed in 28 cities (55%) of 51. The most significant increase in concentrations in the air occurred in Kherson, Lutsk, Donetsk and Gorishni Plavni. In 13 cities reduction of concentrations was recorded, and in 10 cities the content of this pollutant in the air practically does not change.